Liver transplantation for mitochondrial DNA depletion syndrome caused by MPV17 deficiency: a case report and literature review - Wei, Liu-Yuan; Chen, Xiu-Qi; Huang, Li; Shan, Qing-Wen; Tang, Qing (Frontiers in Surgery, 2024)
To study the effectiveness of liver transplantation (LT) in treating mitochondrial DNA depletion syndrome (MDS) caused by the MPV17 gene variant.Case presentation: A boy aged 2.8 years presented with edema of the lower limbs and abdomen, which persisted for over 10 days and was of unknown origin; this was accompanied by abnormal liver function, intractable hypoglycemia, and hyperlactatemia. During the second week of onset, he developed acute-on-chronic liver failure and was diagnosed with MDS due to homozygous variant c.293C>T in the MPV17 gene. Subsequently, he underwent LT from a cadaveric donor. At follow-up after 15 months, his liver function was found to be normal, without any symptoms. Additionally, a literature review was performed that included MDS patients with the MPV17 variant who underwent LT. The results demonstrated that the survival rates for MDS patients who underwent LT were 69.5%, 38.6%, 38.6%, and 38.6% at 1-year, 5-year, 10-year, and 20-year intervals, respectively. Subgroup analyses revealed the survival rate of MDS patients with isolated liver disease (83.33%, 5/6) was higher than that of hepatocerebral MDS patients (44.44%, 8/18). Fifteen variants were identified in the MPV17 gene, and patients with the c.293C>T (p.P98L) variant exhibited the highest survival rate.Hepatocerebral MDS patients without neurological symptoms may benefit from LT.